2008
DOI: 10.1021/om700871p
|View full text |Cite
|
Sign up to set email alerts
|

7-Azaindol-7-ylborate: A Novel Bidentate N^BH3Chelating Ligand

Abstract: 7-Azaindole (H-azain) reacts with sodium borohydride (NaBH4) to yield the sodium salt of the novel 7-azaindol-7-ylborate anion (7-azain-7)BH3 −, two rhodium derivatives of which reveal distinct coordination modes  [Rh{κ2 N,H-H3B(7-azain-7)}(CO)(PPh3)2] and [Rh{κ3 N,H,H′-H3B(7-azain-7)}(PPh3)2]thereby demonstrating how the variable denticity of the ligand may accommodate the varying electronic requirements of the metal center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
45
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 45 publications
4
45
0
9
Order By: Relevance
“…The SiÀN bond lengths (1.888(3)-1.917(5) ) are in a typical range for SiÀN bonds in hexacoordinate Si compounds, and the same applies to the SiÀCl bonds (2.151 (1)-2.211(4) ) with the longer Si À Cl bonds being in the Pt complexes, which exhibit a notably shorter trans-disposed M À Si bond. This Si À Cl bond elongation already hints at pronounced donor strength of the Pt atom in [ClSi(m-mt) 4 PtCl]. Further evidence is provided below.…”
Section: Jörg Wagler* and Erica Brendlermentioning
confidence: 76%
See 4 more Smart Citations
“…The SiÀN bond lengths (1.888(3)-1.917(5) ) are in a typical range for SiÀN bonds in hexacoordinate Si compounds, and the same applies to the SiÀCl bonds (2.151 (1)-2.211(4) ) with the longer Si À Cl bonds being in the Pt complexes, which exhibit a notably shorter trans-disposed M À Si bond. This Si À Cl bond elongation already hints at pronounced donor strength of the Pt atom in [ClSi(m-mt) 4 PtCl]. Further evidence is provided below.…”
Section: Jörg Wagler* and Erica Brendlermentioning
confidence: 76%
“…Within the past decade numerous examples of metallaboratranes followed and have been reviewed and commented on recently. [3] Although further buttressing clamps (e.g., 7-azaindole instead of methimazole) [4] are under investigation for metallaboratrane syntheses, these still rely on the oxidative addition of a B À H bond. The direct formation of metallametallatranes, that is, cage compounds comprising Au!B, Au!Ga, and Au!Al interactions (III), was reported by Bourissou et al [5] Braunschweig et al reported on the compounds IV and V exhibiting Pt 0 !Al III and Pt 0 !Be II interactions (Scheme 1, bottom) and related gallium-containing systems as examples for the straightforward formation of TM!E interactions (E = main-group element), [6] and Fischer et al reported compounds containing Rh I !Ga III bonds.…”
Section: Jörg Wagler* and Erica Brendlermentioning
confidence: 99%
See 3 more Smart Citations